A comparative study of the effect of compression ratio on the efficiency and flame development angle in a Cooperative Fuel Research engine fueled with binary gasoline–alcohol blends. (February 2021) - Rubio-Gómez, Guillermo; Corral-Gómez, Lis; Rodriguez-Rosa, David; Sánchez-Cruz, Fausto A; Martínez-Martínez, Simón
In the last few years, increasing concern about the harmful effects of the use of fossil fuels in internal combustion engines has been observed. In addition, the limited availability of crude oil has driven the interest in alternative fuels, especially biofuels. In the context of spark ignition engines, bioalcohols are of great interest owing to their similarities and blend capacities with gasoline. Methanol and ethanol have been widely used, mainly due to their knocking resistance. Another alcohol of great interest is butanol, thanks to its potential of being produced as biofuel and its heat value closer to gasoline. In this study, a comparative study of gasoline–alcohol blend combustion, with up to 20% volume, with neat gasoline has been carried out. A single-cylinder, variable compression ratio, Cooperative Fuel Research-type spark ignition engine has been employed. The comparison is made in terms of fuel conversion efficiency and flame development angle. Relevant information related to the impact in the combustion process of the use of the three main alcohols used in blends with gasoline has been obtained.